Punk's not dead, even at the Czech Arctic Scientific Station in Svalbard - Zdeněk Lyčka; Josef Elster (Oceanologia, 2020)
Summary: In the last few years, the newly opened Czech Arctic Scientific Infrastructure in Svalbard – Josef Svoboda Station – has closely collaborated with UiT – The Arctic University of Norway on very productive research related to climate change and the impact of the sea and land ice disappearance. Professor Josef Elster, the Head of the Czech station and a researcher in the diversity, ecology and ecophysiology of polar algae and cyanobacteria, and the glacial microbiologist Marie Šabacká and their team try to find the answer to questions concerning how the Arctic ecosystem responds to global warming and how global warming affects human activity. The results of their research can be used, for example, in the treatment and refinement of drinking and sewage water, the pharmaceutical industry and medicine, livestock nutrition including aquaculture and in the production of nutritional supplements for people. However, even the most exciting scientific information and results are not readily available to a non-professional audience. Interdisciplinarity and a suitable cultural framework can bring new life to the results of scientific research. If the presentation of science is interconnected with cultural disciplines such as literature, art, music or theatre, its account can be enriched and media interest can be increased. The scientific-cultural festivals AT HOME IN SVALBARD 2018 and ARCTIC FESTIVAL 2019 are just two good examples. The presentation of scientific research through culture is a very distinctive and innovative attempt. Moreover, the interest of the public can influence the stakeholders’ approach to providing and increasing finances for further scientific research.